Mu-opioid Receptor (MOR) Biased Agonists Induce Biphasic Dose-dependent Hyperalgesia and Analgesia, and Hyperalgesic Priming in the Rat. (1st December 2018) - Araldi, Dionéia; Ferrari, Luiz F.; Levine, Jon D.
Highlights: Intradermal administration of biased MOR agonists produces opioid-induced hyperalgesia (OIH) and hyperalgesic priming. While systemic administration of low doses of biased MOR agonist produces hyperalgesia, high doses induce analgesia. OIH and hyperalgesic priming induced by local or systemic administration of biased MOR agonists are MOR dependent. Biased MOR agonist-induced priming has a different maintenance mechanism than that established for Type I and II priming. Abstract: Stimulation of the mu-opioid receptor (MOR) on nociceptors with fentanyl can produce hyperalgesia (opioid-induced hyperalgesia, OIH) and hyperalgesic priming, a model of transition to chronic pain. We investigated if local and systemic administration of biased MOR agonists (PZM21 and TRV130 [oliceridine]), which preferentially activate G-protein over β-arrestin translocation, and have been reported to minimize some opioid side effects, also produces OIH and priming. Injected intradermally (100 ng), both biased agonists induced mechanical hyperalgesia and, when injected at the same site, 5 days later, prostaglandin E2 (PGE2 ) produced prolonged hyperalgesia (priming). OIH and priming were both prevented by intrathecal treatment with an oligodeoxynucleotide (ODN) antisense (AS) for MOR mRNA. Agents that reverse Type I (the protein translation inhibitor cordycepin) and Type II (combination of Src and mitogen-activated protein kinase [MAPK] inhibitors) priming, or their combination, did not reverse priming induced by local administration of PZM21 or TRV130. While systemic PZM21 at higher doses (1 and 10 mg/kg) induced analgesia, lower doses (0.001, 0.01, 0.1, and 0.3 mg/kg) induced hyperalgesia; all doses induced priming. Hyperalgesia, analgesia and priming induced by systemic administration of PZM21 were also prevented by MOR AS-ODN. And, priming induced by systemic PZM21 was also not reversed by intradermal cordycepin or the combination of Src and MAPK inhibitors. Thus, maintenance of priming induced by biased MOR agonists, in the peripheral terminal of nociceptors, has a novel mechanism.